2012
DOI: 10.1007/jhep10(2012)021
|View full text |Cite
|
Sign up to set email alerts
|

Towards a holographic realization of Homes’ law

Abstract: Gauge/gravity duality has proved to be a very successful tool for describing strongly coupled systems in particle physics and heavy ion physics. The application of the gauge/gravity duality to quantum matter is a promising candidate to explain questions concerning non-zero temperature dynamics and transport coefficients. To a large extent, the success of applications of gauge/gravity duality to the quark-gluon plasma is founded on the derivation of a universal result, the famous ratio of shear viscosity and en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 61 publications
3
49
0
4
Order By: Relevance
“…[19] for the deconfinement temperature). (v) Among theoretical challenges for the holographic superconductors one can mention the problem of a dual gravitational interpretation for the empirical Homes' scaling law in the high-T c superconductors [20] (see [21,22] for a discussion from the holographic perspective). Our preliminary analysis showed that this law imposes rather strong constraint on the mutual dependence of the model parameters and seems to prescribe for them a certain temperature dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] for the deconfinement temperature). (v) Among theoretical challenges for the holographic superconductors one can mention the problem of a dual gravitational interpretation for the empirical Homes' scaling law in the high-T c superconductors [20] (see [21,22] for a discussion from the holographic perspective). Our preliminary analysis showed that this law imposes rather strong constraint on the mutual dependence of the model parameters and seems to prescribe for them a certain temperature dependence.…”
Section: Discussionmentioning
confidence: 99%
“…If we take the point of view that in the holographic approach, which is inherently large-N one, only quadratic in fields part is relevant, then we should either assume r 0 = 0 in (22), i.e. somehow motivate pure AdS metric in (21), or exclude the interaction term. In the latter case, the equation of motion for ϕ = ϕ(r ),…”
Section: Soft Wall Holographic Superconductormentioning
confidence: 99%
“…The holographic theory of Refs. [73,74] claimed its success with finding the prefactor C ≈ 6.2 to be close to the experimental values in the cuprates which happen to be C ≈ 8.1 and 4.4 for the ab-and c-axes transport, respectively. Somewhat ironically, though, this would seem like a case where, in the absence of a compelling underlying reason, a perfect quantitative agreement could do more harm than good to the cause.…”
Section: D+z-θmentioning
confidence: 64%
“…Besides, it was also argued to be intermittent with the alternate 'universal' , ~ω -1 , behaviour. Another notable example is the holographic calculation [73,74] of the numerical prefactor C in the empirical Homes relation between the superfluid density, critical temperature, and normal state conductivity [75]:…”
Section: D+z-θmentioning
confidence: 99%
“…There is a mapping between observables in the superconducting system and fields in the corresponding extra-dimensional model. Progress has been made in understanding properties of holographic models of superconductors and other condensed matter systems, including s, p, and d-wave superconductivity [8][9][10], the Nernst effect in the quantum critical regime [11], strange metallic behavior [12], enhancement of the superconducting gap compared to BCS theory [13], and Homes's empirical law for T c as a function of low-temperature superfluid density and normal-phase resistivity [14,15]. In some models of holographic superconductors there is no hard zero-temperature gap [16].…”
Section: Introductionmentioning
confidence: 99%